2020
DOI: 10.3389/fmicb.2020.01795
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses in the Sea

Abstract: Interest in coronaviruses because of the 2019 novel coronavirus (SARS-CoV-2) pandemic has generated concern about their occurrence and persistence in aquatic habitats. Coronaviruses are not quantitatively significant constituents of marine virioplankton. Members of the Nidovirales (to which human coronaviruses belong) infect marine mammals, teleosts and possibly invertebrates, and human coronaviruses may persist in marine plankton receiving wastewater effluent. However, virions likely experience significant pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
0
31
0
2
Order By: Relevance
“…Alignment of the A. californicus flavivirus-like genome fragment against closest matches at NCBI revealed that it was firmly embedded within a clade of insect-specific flaviviruses [51], including flaviviruses recovered from cephalopods [52] and from invertebrate and vertebrate transcriptomes [53] ( Figure 2). Enveloped RNA viruses are notable in marine ecosystems because they are not common constituents of virioplankton and generally experience high decay rates in seawater [54]. Flaviviruses (+ssRNA) represent important pathogens of mammals, including Dengue Fever, Yellow Fever, Hepatitis C Virus and Zika Virus.…”
Section: Flavivirus-like Genome Fragmentmentioning
confidence: 99%
“…Alignment of the A. californicus flavivirus-like genome fragment against closest matches at NCBI revealed that it was firmly embedded within a clade of insect-specific flaviviruses [51], including flaviviruses recovered from cephalopods [52] and from invertebrate and vertebrate transcriptomes [53] ( Figure 2). Enveloped RNA viruses are notable in marine ecosystems because they are not common constituents of virioplankton and generally experience high decay rates in seawater [54]. Flaviviruses (+ssRNA) represent important pathogens of mammals, including Dengue Fever, Yellow Fever, Hepatitis C Virus and Zika Virus.…”
Section: Flavivirus-like Genome Fragmentmentioning
confidence: 99%
“…In a manner similar to many animals, these mammals are susceptible to other coronaviruses [90], and therefore there is concern about them being infected with SARS-CoV-2 [91]. With it being known that SARS-CoV-2 can exist in human faeces [92] it has been determined that the virus can survive transiently in wastewater [93] and seawater [94] although it has been disputed that this a significant route of virus transmission in the environment [95]. Although this might not sound too alarming, there is still the potential for marine mammals to be in contact with the virus near sewage outlets.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that some surveillance of species in areas where the wastewater treatment is suboptimal may be important in the future. However, other enveloped RNA viruses have been shown to experience declines in viral titres upon exposure to seawater, implying that the salt content and natural dilution that would occur in seawater would likely minimize the risk of the spread of SARS-CoV-2 to aquatic life [ 89 ].…”
Section: Areas For Further Investigationmentioning
confidence: 99%